Effect of Positive Mindfulness and Emotion-Focused Cognitive-Behavioral Therapy in Fibromyalgia Patients’ Response to Stress and Subjective Well-Being - Jahanshahi Hesari, Nahid; Asgari, Parviz; Naderi, Farah; Heidari, Alireza (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Fibromyalgia disease has a considerable effect on anxiety disorders such as subjective well-being. The present study aimed to investigate the effect of positive mindfulness therapy (PMT) and emotion-focused cognitive-behavioral therapy (EFCBT) in fibromyalgia patients’ response to stress and subjective well-being. Methods: The research method was quasi-experimental with a pre-test and post-test design, and a control group. The statistical population included 160 women with fibromyalgia, visiting Red Cross affiliated physiotherapy clinics in Tehran in 2020. The sample consisted of 60 patients with fibromyalgia selected by convenience sampling and randomly divided into two experimental groups (PMT and EFCBT) and a control group (n= 20 per group). Data were collected using the Self-Regulation Inventory (SRI) and the Subjective Well-Being Scale. The validity and reliability of the research instruments were confirmed. Data were analyzed at descriptive and inferential levels using SPSS software version 20. Results: The results showed that the PMT produced significant improvements in subjective well-being and response to stress (P = 0.001) in patients with fibromyalgia. Furthermore, EFCBT was effective in improving subjective well-being and response to stress (P = 0.001) in the patients compared to the control group. The results did not imply a significant difference between the two treatment interventions. Conclusions: PMT and EFCBT were effective in reducing response to stress and improving subjective well-being in patients with fibromyalgia. Based on the results, holding PMT and EFCBT workshops may exert beneficial effects on reducing response to stress and increasing subjective well-being in patients with fibromyalgia. According to the results, using positive mindfulness therapy and emotion-focused cognitive-behavioral therapy was effective in reducing response to stress and improving subjective well-being in patients with fibromyalgia.